Odpowiedzi

2010-04-13T19:56:14+02:00
A. 3x-1=y-2
4x-3=2y-4

3x-y=-2+1
4x-2y=-4+3

3x-y=-1/*(-2)
4x-2y=-1

-6x+2y=-2
4x-2y=1

-2x=-1/:(-2)
x=0,5

3*0,5-y=1
1,5-y=1
1,5-1=y
0,5=y

x=0,5
y-0,5



b. 2x+2y-(x-1)=y=2
x+y=1
2x+2y-x-1=y+2
x+y=1
2x-x+2y-y=2+1
x+y=1
x+y=3/*(-1)
x+y=1
-x-y=3
x+y=1
0=4



Rozwiązałam a i b ale nie wiem czy są dobrze
1 2 1
2010-04-13T20:04:04+02:00
1.)
3x - 1 = y - 2
4x - 3 = -2(y - 2)

3x-y= -2+1
4x-3= -2y +4

3x-y = -1 / *2
4x+2y= 7

6x-2y= -2
+ 4x+2y= 7
10x = 5 /:10
x= 0,5

6x-2y=-2
x=0,5

3-2y=-2
x=0,5

2y=-2-3
x=0,5

2y=-5 / :2
x=0,5

y=-2,5
x=0,5

2.)

2(x + y) - (x - 1) = y + 2
x + y = 1

2x+2y-x+1=y+2
x+y=1

x+y=2-1
x+y=1

x+y=1
x+y=1

x=0,5
y=0,5

Nie jestem pewny czy dobrze. Już dawno temu to miałem ;)








1 2 1